The effect of joint stiffness on optimization design strategies for gridshells: The role of rigid, semi-rigid and hinged joints. (February 2023) - Tomei, Valentina
Abstract: Structural optimization techniques are becoming popular and effective approaches for the design of constructions, able to support architects and structural designers in the complex process of searching competitive solutions, usually in terms of structural weight, cost and accounting for specific structural/functional requirements. In case of gridshells, the structural weight is strictly related to the susceptibility of the structure to global buckling, which is often the governing design criterion. The susceptibility to global buckling is mainly due to the global stiffness of the structures, primarily related to the stiffness of the joints, to the boundary conditions, and to the presence of imperfections. In this context, the paper presents design strategies based on optimization techniques that specifically take into accounts the presence of semi-rigid, rigid and hinged joints in order to guarantee light solutions safe from global buckling phenomena. In particular, two approaches are proposed: the joint stiffness approach, which considers the gridshell composed by semi-rigid joints, all characterized by the same rotational stiffness, and the rigid/hinged approach, which considers the gridshell composed by most hinged joints, and by a low number of rigid joints arranged in optimal positions. The approaches have been applied to a case study characterized by different boundary conditions, different rise-to-span ratios and also considering both perfect and imperfect shapes. The results of the proposed optimization processes highlight the beneficial effect of a finite value of the rotational stiffness of the joints in the susceptibility of the gridshell to global buckling phenomena, leading to light structural solutions.